The applying accounting methodology of radar chart for textile production activity in Great Britain - Benedito, Miguel Angel Pérez (Archives of Business Research, 2018)
The manuscript analyses the management of textile industrial on several countries applying accounting methodology of radar charts. The answer of companies to changes of markets are kinds of management obtained from financial statements when average periods of maturation are axes of a radar chart. Distances between consecutives axes of a radar chart are perimeter distances, which measure tension that transactions entail on respective management areas represented on it. The orientation of perimeter distances measured by internal angles allows obtaining necessary and sufficiency conditions to assess kinds of management respect to accounting financial structures of companies. These relations are visual represented avoiding to apply stochastic methods for analysis. This cause-effect relation supposes there are cultural factors where companies are located, which make conditional on time of conducting business transactions.